Indigenous Tourism (Case Study Tidore City Island) - Dewi, Liliana (SABA: Journal of Tourism Research, 2023)
Indigenous tourism is a term that is not commonly heard and applied by most tourism actors in the region to develop regional potential. The level of kinship and Islamic faith-based customs that are still firmly held amid the development of globalization make Tidore Islands City unique to develop tourism in the region. The purpose of this study is to examine 1) the potential development of tourism products in Tidore Kepualauan, 2) assess the impact of tourism activities from a socio-cultural, economic and environmental point of view. Data were collected by two means of qualitative research methods. Data were obtained from interviews and literature studies. The results of the study are known that Tidore Islands City has potential varieties that can be made into a tourist product, such as cultural tourism products, local people and nature are the main points that can attract domestic tourists. The impact of tourism activities on socio-cultural and environmental, economic and environmental is significantly changing.